Educação na primeira infância nas classes populares: semelhanças e distinções da creche e pré-escola nas zonas urbana e rural no município de São José de Ribamar-MA - MOREIRA, Maysa Barbosa (2023)
This dissertation has as its starting point the answer to the following question: what is the importance of day care centers and public preschools for families from the popular classes in the municipality of São José de Ribamar-MA? Which also implies trying to answer whether there are differences in roles between the referred school units in the urban and rural areas of that municipality. To answer such questions, based on a bibliography relevant to the subject, a survey was carried out with those school communities (managers and families), aiming to capture elements that would answer these questions, taking into account how education is offered and accessed in the first childhood in a municipality that is part of the metropolitan region of São Luís. As for the method used, comparative reasoning was chosen, since it consists of observing and comparing existing or existing educational systems, with a view to apprehending their common characteristics and making it possible to reach a precise definition of the educational phenomenon. In general terms, with the development of research and data analysis, always taking into account the social character of education already pointed out by Émile Durkheim, it was verified that day care centers and preschools are essential for families, even if they exist difficulties in accessing vacancies made available by school units in the countryside and in the city, due to the low number of enrollments by the municipal body responsible for education, as recommended by current legislation. To arrive at these and other findings, the present dissertation discussed the sociogenesis of family and childhood, the interdependence relationships between family and school, the social construction of gender and day care and/or public preschool for women and families and the meaning of the public schools of early childhood education in urban and rural areas of the municipality of São José de Ribamar-MA.